Measurement of light-by-light scattering and search for axion-like particles with 2.2 nb-1 of Pb+Pb data with the ATLAS detector (vol 2021, 243, 2021) - Aad, G.; Abbott, B.; Abbott, D. C.; Abed Abud, A.; Abeling, K.; Abhayasinghe, D. K.; Çetin, Serkant Ali (Springer, 2021)
[Abstract Not Available]